Animal board invited review: The effect of diet on rumen microbial composition in dairy cows - A. Palmonari; A. Federiconi; A. Formigoni (Animal, 2024)
Ruminants play an important part in the food supply chain, and manipulating rumen microbiota is important to maximising ruminants’ production. Rumen microbiota through rumen fermentation produces as major end products volatile fatty acids that provide animal’s energy requirements, and microbial CP. Diet is a key factor that can manipulate rumen microbiota, and each variation of the physical and chemical composition creates a specific niche that selects specific microbes. Alteration in the chemical composition of forage, the addition of concentrates in the diet, or the inclusion of plant extract and probiotics, can induce a change in rumen microbiota. High-throughput sequencing technologies are the approaches utilised to investigate the microbial system. Also, the application of omics technologies allows us to understand rumen microbiota composition and these approaches are useful to improve selection programmes. The aim of this review was to summarise the knowledge about rumen microbiota, its role in nutrient metabolism, and how diet can influence its composition.